New advances in liver decellularization and recellularization: innovative and critical technologies. (October 2015) - Lin, Yi-Qian; Wang, Li-Ren; Wang, Jiang-Tao; Pan, Liang-Liang; Zhu, Gui-Qi; Liu, Wen-Yue; Braddock, Martin; Zheng, Ming-Hua
Abstract : Techniques for producing decellularized scaffolds for use in liver tissue engineering are emerging as promising methods for tissue reconstruction. In this article, the authors present an overview of liver decellularization methods developed and applied in recent years. These include the widespread use of various perfusion methods for the generation of a 3D scaffold, which may function as a template for either cell recellularization or direct biological application. The authors evaluate methods for scaffold production and explore some factors that may affect the decellularization process. In addition to tissue engineering, this overview includes a description of other potential applications for a decellularized liver scaffold. The authors also introduce the concept of fabrication of fragile biomaterial architecture and finally review the cell types applied to liver scaffold engineering.